Organizational Culture and Digital Engagement: Study at Hospital X, Integrative Model - Savitri, Anastasia; Mas'ud, Fuad (LifeSciFi, 2025)
Digital transformation in healthcare creates structural and cultural challenges, especially in institutions prioritizing interpersonal service. Hospital X has implemented limited digital services, such as WhatsApp teleconsultation, despite increasing patient demand—mainly from pre-elderly individuals—for digital accessibility. Using an exploratory qualitative approach, this study interviewed seven employees from clinical, administrative, and IT functions. Findings reveal limited digitalization due to strong humanistic values, low digital competency, the absence of a structured transformation plan, and minimal employee involvement in innovation. Resistance stems not only from technical issues but also from cultural and emotional factors. To address this, a five-pillar integrative model is proposed: (1) recontextualizing values, (2) engaging employees in innovation, (3) gradual digital literacy training, (4) transparent communication, and (5) feedback-driven evaluation. This model offers a practical framework for balancing human-centered values with digital advancements in healthcare institutions.